Design and construction of single guide RNA for CRISPR/Cas9 system based on the xa13 resistance gene in some varieties of rice (Oryza sativa) - Hardiyani, Wulan Arum; Wafa, Ali; Fanata, Wahyu Indra Duwi; Addy, Hardian Susilo (Universitas Lampung, 2023)
The xa13 gene is a recessive resistance gene against Xanthomonas oryzae pv. oryzae (Xoo) found in several rice varieties. Activation of this gene will trigger the formation of sucrose as a nutrient supply to Xoo for their growth in the plant. The disruption of this recessive gene expression in the plant can affect the negative impact of the gene, and recently can be created using clustered regularly interspaced short palindromic repeats (CRISPR) system using CRISPR-associated protein-9 (CRISPR/Cas9) technology that requires gRNA to recognize the targeted-sequence. This study aimed to design and construct the gRNA-targeting xa13 gene in rice using bioinformatics tools. CHOPCHOP was used for generated the gRNA candidates according to the target gene sequence. Two candidates of gRNA-targeted xa13 have been selected based on the analysis of bioinformatics data. Each candidate of gRNA consisted of 20 nucleotides (nt) of the target sequence upstream 3 nt of the protospacer adjacent motif (PAM) sequence (5’-NGG) targeting two exons in the xa13 gene. The gRNA1 will target exon 1 and the gRNA2 will target exon 2, with an efficiency of 52.51% and 44.63% respectively. Data showed that the GC content of all gRNA candidates ranged from 55–70% with no target-off location in the whole genome of rice. The transformation and confirmation test based on the physiological and genomic characteristics of transformants confirmed that the design has been successfully constructed.